Atoms‐in‐molecules analysis of the effect of intermolecular interactions on dielectric properties in hydrogen‐bonded material 5‐bromo‐9‐hydroxyphenalenone. Issue 3 (13th March 2012) - Otaki, Hiroki; Ando, Koji; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Intermolecular interactions in molecular crystal of 5‐bromo‐9‐hydroxyphenalenone are analyzed by means of Bader's theory of atoms in molecules. A set of criteria to ascertain the presence of a hydrogen bond is applied to two candidates of intermolecular contacts suggested by our previous work [Otaki and Ando, Phys. Chem. Chem. Phys. 2011, 13, 10719]. It is shown that they almost satisfy the criteria to confirm the existence of intermolecular CH···O hydrogen bond. In addition to the hydrogen bonding, other types of interactions, such as H···H and H···Br, are found in one of the candidates. The discussions are extended to explain how the molecular dipole moment is induced by surrounding molecules. It is also found that the bias in the atomic charges due to the electrophilicity of the oxygen atom is strongly correlated with the induced dipole moment. © 2012 Wiley Periodicals, Inc.